2012
DOI: 10.1016/j.jnucmat.2012.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and dissociation of H2O on Zr(0001) with density-functional theory studies

Abstract: The adsorption and dissociation of isolated H 2 O molecule on Zr(0001) surface are theoretically investigated for the first time by using density-functional theory calculations. Two kinds of adsorption configurations with almost the same adsorption energy are identified as the locally stable states, i.e., the flat and upright configurations respectively. It is shown that the flat adsorption states on the top site are dominated by the 1b 1 -d band coupling, insensitive to the azimuthal orientation. The diffusio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…This agrees well with the previous DFT study which suggested that the lowest energy path is the bri site dissociation. 12 The structure images of the CI-NEB paths are plotted in Figures 4−6. For the bri path, the H 2 O molecule first slightly moves toward the hcp site and tilts, as shown in Figure 4a− The dissociation path of the top-f path is similar to that along the top-h path, as shown in Figure 6.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This agrees well with the previous DFT study which suggested that the lowest energy path is the bri site dissociation. 12 The structure images of the CI-NEB paths are plotted in Figures 4−6. For the bri path, the H 2 O molecule first slightly moves toward the hcp site and tilts, as shown in Figure 4a− The dissociation path of the top-f path is similar to that along the top-h path, as shown in Figure 6.…”
Section: Resultsmentioning
confidence: 99%
“…Five atomic Zr layers were adopted in the slab model with the bottom two layers fixed and the three top layers are free to relax in simulations. The five-layer model is enough to study the water dissociation mechanism on the Zr (0001) surface . A 20 Å vacuum region was applied in the slab model to avoid the interaction between replicated images.…”
Section: Computational Methodsmentioning
confidence: 99%
See 3 more Smart Citations